2018
DOI: 10.3390/ijms20010012
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Watermelon HSP20s and Their Expression Profiles and Subcellular Locations under Stresses

Abstract: Watermelon (Citrullus lanatus L.), which is an economically important cucurbit crop that is cultivated worldwide, is vulnerable to various adverse environmental conditions. Small heat shock protein 20s (HSP20s) are the most abundant plant HSPs and they play important roles in various biotic and abiotic stress responses. However, they have not been systematically investigated in watermelon. In this study, we identified 44 watermelon HSP20 genes and analyzed their gene structures, conserved domains, phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…In the present study, we identified 41 HSP20 genes and investigated their characteristics from the apple genome database. The number of apple HSP20 genes was higher than that of Arabidopsis (19) (Scharf et al, 2001), slightly higher than rice (39) (Ouyang et al, 2009) but lower than that of watermelon (44) (He et al, 2019), potato (48) (Zhao et al, 2018), and grape (48) (Ji et al, 2019). This difference is most likely due to the fact that apple had gene duplications during evolution (Velasco et al, 2010;Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we identified 41 HSP20 genes and investigated their characteristics from the apple genome database. The number of apple HSP20 genes was higher than that of Arabidopsis (19) (Scharf et al, 2001), slightly higher than rice (39) (Ouyang et al, 2009) but lower than that of watermelon (44) (He et al, 2019), potato (48) (Zhao et al, 2018), and grape (48) (Ji et al, 2019). This difference is most likely due to the fact that apple had gene duplications during evolution (Velasco et al, 2010;Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Plants have developed a series of physiological and molecular strategies to overcome temperature stress over evolutionary time ( Asea et al, 2016 ; Huo et al, 2020 ). Heat shock proteins (HSPs) are one of the strategies, and HSPs are essential in regulating growth, development and stress response in plants ( Waters et al, 1996 ; Wang et al, 2004 ; Asea et al, 2016 ; He et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the HSP20 gene family have been investigated in many plants, such as Arabidopsis, rice, soybean, watermelon, pepper and tomato. There are 19 HSP20 genes in Arabidopsis [11], 39 in rice [18], 51 in soybean [19], 44 in watermelon [20], 35 in pepper [21] and 42 in tomato [22]. To date, HSP20 gene family members of the grape have not been identified.…”
mentioning
confidence: 99%
“…The number of Hsp20 genes in plants is about four times greater than that in animals [17]. For example , 19, 35, 39, 42, 44, 51 members of the Hsp20 gene family were respectively investigated in Arabidopsis (Arabidopsis thaliana) [11], pepper (Capsicum annuum L.) [18], rice (Oryza sativa) [19], tomato (Solanum lycopersicum) [20], watermelon (Citrullus lanatus L.) [21], and soybean (Glycine max) [22]. To date, Hsp20 gene family members in grape have not been identified.…”
mentioning
confidence: 99%